Small peptide signaling pathways modulating macronutrient utilization in plants. (October 2017) - de Bang, Thomas C; Lay, Katerina S; Scheible, Wolf-Rüdiger; Takahashi, Hideki
Highlights: Small signaling peptides and cognate receptors play key roles in nutrient acquisition. Local and systemic nutrient signals control expression of small signaling peptides. Small signaling peptides systemically control nodule development and root functions. Advanced genome annotation and RNAseq identify novel peptides for nutrient signaling. Abstract : Root system architecture (RSA) and physiological functions define macronutrient uptake efficiency. Small signaling peptides (SSPs), that act in manners similar to hormones, and their cognate receptors transmit signals both locally and systemically. Several SSPs controlling morphological and physiological traits of roots have been identified to be associated with macronutrient uptake. Recent development in plant genome research has provided an avenue toward systems-based identification and prediction of additional SSPs. This review highlights recent studies on SSP pathways important for optimization of macronutrient uptake and provides new insights into the diversity of SSPs regulated in response to changes in macronutrient availabilities.